2007
DOI: 10.1128/ec.00262-07
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin Induces Calcium-Dependent Protein Secretion in the Protozoan ParasiteToxoplasma gondii

Abstract: Intracellular calcium controls several crucial cellular events in apicomplexan parasites, including protein secretion, motility, and invasion into and egress from host cells. The plant compound thapsigargin inhibits the sarcoplasmic-endoplasmic reticulum calcium ATPase (SERCA), resulting in elevated calcium and induction of protein secretion in Toxoplasma gondii. Artemisinins are natural products that show potent and selective activity against parasites, making them useful for the treatment of malaria. While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 55 publications
4
103
0
1
Order By: Relevance
“…The inability of artemisinin to inhibit merozoite invasion was somewhat surprising given reports that this drug binds to SERCA (sarcoplasmic/endoplasmic reticulum calcium ATPase), a calcium ATPase with a role in microneme release during invasion in Toxoplasma gondii (35). In vitro binding of artemisinin to ATPase 6, the SERCA homologue in P. falciparum, has also been reported previously (36).…”
Section: Discussionmentioning
confidence: 97%
“…The inability of artemisinin to inhibit merozoite invasion was somewhat surprising given reports that this drug binds to SERCA (sarcoplasmic/endoplasmic reticulum calcium ATPase), a calcium ATPase with a role in microneme release during invasion in Toxoplasma gondii (35). In vitro binding of artemisinin to ATPase 6, the SERCA homologue in P. falciparum, has also been reported previously (36).…”
Section: Discussionmentioning
confidence: 97%
“…These results indicated that the suppressive effect of matrine on IL-2 mRNA expression in Jurkat T cells did not result from its cytotoxicity. Another compound, artemisinin derived from the medicinal herb Artemisia annua L. demonstrated its potency in anti-inflammation, immune regulation and enhancement of Ca 2ϩ flux, 13,15) and it has been used in many countries for treatment of severe and chloroquineresistant malaria. However, this compound showed no ability to induce T cell anergy (Fig.…”
Section: Validation Of T Cell Anergy Induction Model Inmentioning
confidence: 99%
“…Pyrimethamine inhibits the parasite's dihydrofolate reductase enzyme (11), while artemisinin appears to perturb calcium homeostasis in the parasite (27). Tgmsh-1 mutant parasites are not resistant to either of these drugs (E. M. Garrison and G. Arrizabalaga, unpublished observations).…”
mentioning
confidence: 99%